Метод многокритериально-вариационной оптимизации озонометрических измерений в прибрежных зонах - Асадов, Хикмет Гамид; Зейналова, Шана Низами (НТУ "ХПИ", 2016)
Предложен метод многокритериально-вариационной оптимизации для решения специализированных задач физики атмосферы, в частности для многодиапазонных интегрированных озонометрических измерений. Предлагаемый метод предусматривает наложение определенного ограничения на интеграл второго члена взвешанной скалярной суммы частных критериев парафазно зависящих от искомой функции, определяющей условия проведения измерительного эксперимента. Конкретно рассмотрена задача оптимального интегрированного во времени измерения общего количества озона в атмосфере при использовании бортового комплекса, осуществляющего измерения в ультрафиолетовом и видимом диапазонах.

The method of multicriterial-variation optimization is suggested for solution of some specialized tasks of atmospheric physics, particularly for multi-band integrated ozonometric measurements. The suggested method provides for application of some limitation on integral of the second member of weighted scalar sum of partial criterions which concurrently depend on looked for function, determining the conditions of measuring experiment. Concretely the task on optimum integrated measurements of total amount of atmospheric ozone using the onboard measuring complex, carrying out measurements in ultraviolet and visible bands. The optimality is accepted as reaching the extremum of weighted sum of channels signals. The optimum function of noisy effect of atmospheric aerosol providing the optimum measurements is searched for. The optimum function of noises depends on weight function of complexes channels. Such a dependence make it possible to use the weight function of channels as a control function to lead the function into optimum regime of operation by maximum differentiation of noises function from, optimum type of latter.
The method of multicriterial-variation optimization of ozonometric measurements in coastal zones
Keywords: вариационная оптимизация; измерения; свертка; атмосфера; озонометрия; многокритериальная оптимизация; variation optimization; measurements; convolution; atmosphere; ozonometrics; multicriterial optimization